2021
DOI: 10.1253/circrep.cr-21-0099
|View full text |Cite
|
Sign up to set email alerts
|

Ablation Index-Guided High-Power Radiofrequency Application Shortens the Procedure Time With Similar Outcomes to Conventional Power Application in Atrial Fibrillation Ablation

Abstract: Background:The impact of high-power radiofrequency (RF) application in ablation index (AI)-guided atrial fibrillation (AF) ablation has not been elucidated. Methods and Results:We investigated 1,333 patients undergoing first AF ablation (median age 68 years; interquartile range [IQR] 61-73 years). The first 301 patients underwent AI-guided conventional power RF application (CP group), whereas the following 1,032 patients underwent high-power RF application (HP group). The minimum AI target values were 400, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Included Studies and Their Quality Assessment. According to the established searching strategy, 1240 potential relative literatures were identified from PubMed, Embase, and Cochrane Library and from which 22 studies were included in this meta-analysis after full-text review of 47 articles as shown in Figure 1 [7,8,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. There were 9 retrospective studies, 10 prospective studies, 1 randomized nonblinded study, and 2 randomized controlled trials (RCTs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Included Studies and Their Quality Assessment. According to the established searching strategy, 1240 potential relative literatures were identified from PubMed, Embase, and Cochrane Library and from which 22 studies were included in this meta-analysis after full-text review of 47 articles as shown in Figure 1 [7,8,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. There were 9 retrospective studies, 10 prospective studies, 1 randomized nonblinded study, and 2 randomized controlled trials (RCTs).…”
Section: Resultsmentioning
confidence: 99%
“…Efficacy Endpoints of High-Power Short-DurationAblation Strategies. First-pass PVI rate was pooled from 13 studies[19,21,[24][25][26][27][28][29][30][31][32][33]37]. Patients underwent HPSD ablation showed higher first-pass PVI rate during procedure compared with conventional group (RR = 1:10, 95% CI: 1.05-1.15, I 2 = 56%, and P = 0:0001) (Figure2(a)).…”
mentioning
confidence: 99%
“…The aprons are worn under the sterile gowns during the entire procedure. Durations to implant CRT device commonly extend from 1.5 to 2.5 h for CRT device implants [15,30], while ablation of atrial fibrillation or ventricular tachycardia (VT) may range from 2.5 to 6 h [31][32][33]. Hanging lead aprons from ceiling-mounted devices makes EP lab construction cumbersome while not protecting the EP lab support staff or the industry device representative.…”
Section: Metrics-procedural Radiation Reduction and The Missing Lead ...mentioning
confidence: 99%
“…In recent years, the ablation index (AI) has been widely applied to treat drug-resistant paroxysmal AF [7]. AI is known as a novel quantitative ablation lesion marker that combines contact force (CF), time, and power in a weighted formula [8,9]. In recent studies, patients undergoing AIguided ablation of AF have good clinical outcomes, and the procedure time and ablation time are relatively short; meanwhile, it is considered a feasible and safe technique [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent animal studies, 50 W/5 seconds was superior to LPLD ablation for lesion creation with lower complication rates [17,20]. In AI-guided high-power (50 W) ablation, the time to complete PVI is shorter, with higher first-pass isolation rate, lower left atrial-(LA-) PV reconnection rate, and no increase in complications, so it is considered a safe and feasible ablation technique [9,[21][22][23]. But reports on the safety and efficacy of AI-guided high-power RF ablation for paroxysmal atrial fibrillation are warranted.…”
Section: Introductionmentioning
confidence: 99%